1998
DOI: 10.1063/1.1149247
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient optically pumped NH3 laser with near diffraction limited output

Abstract: We present the design of a highly efficient, pulsed ammonia laser which is optically pumped by a commercial TEA CO2 laser and is line tunable in the spectral range of 780–930 cm−1. The power, spectral, and temporal characteristics of the laser have been investigated for different configurations of the optical cavity. Using a stable resonator, the laser operates with an efficiency of 24% (940 mJ) in a multiline configuration and 16.5% on a single line. Changing the resonator to an unstable configuration produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Depending on the optical configuration of the resonator, the ammonia laser operates either in singleline or multi-line mode. 32 Figure 3 shows the typical output of the laser on the individual lines in single-line mode. In multiline mode, 95% of the energy output occurs on lines below 870 cm -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the optical configuration of the resonator, the ammonia laser operates either in singleline or multi-line mode. 32 Figure 3 shows the typical output of the laser on the individual lines in single-line mode. In multiline mode, 95% of the energy output occurs on lines below 870 cm -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Most research has been dedicated on the assignments of the observed THz laser lines from active molecules [1,2] and improvement of the laser configuration to enhance pumping efficiency and THz output energy [2][3][4][5], in which NH 3 has been proved to be a source of many strong THz laser transitions. However, the ammonia THz radiation has not been strong in the past studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, we reported the results of a study of IRMPD of SiH 4 using both CO 2 and NH 3 lasers . The use of silane as a parent molecule for isotope separation of Si is attractive, since it is widely employed in the semiconductor industry.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, 7 we reported the results of a study of IRMPD of SiH 4 using both CO 2 and NH 3 lasers. 8 The use of silane as a parent molecule for isotope separation of Si is attractive, since it is widely employed in the semiconductor industry. Our study revealed that IRMPD of vibrationally ground-state silane is inefficient, exhibiting a laser fluence threshold that is near 17 J/cm 2 .…”
Section: Introductionmentioning
confidence: 99%